Binaries discovered by the MUCHFUSS project: SDSS J162256.66 + 473051.1: An eclipsing subdwarf B binary with a brown dwarf companion - Schaffenroth, Veronika; Geier, Stephan; Heber, Ulrich; Kupfer, Thomas; Ziegerer, Eva; Heuser, Christian; Classen, Lew; Cordes, O. (Astronomy & Astrophysics, 2014)
Hot subdwarf B stars (sdBs) are core helium-burning stars located on the extreme horizontal branch. About half of the known sdB stars are found in close binaries. Their short orbital periods of 1.2 h to a few days suggest that they are post common-envelope systems. Eclipsing hot subdwarf binaries are rare but are important in determining the fundamental stellar parameters. Low-mass companions are identified by the reflection effect. In most cases, the companion is a main sequence star near the stellar mass limit. Here, we report the discovery of an eclipsing hot subdwarf binary SDSS J162256.66+473051.1 (J1622) with very short orbital period (0.0697 d), which has been found in the course of the MUCHFUSS project. The lightcurve shows grazing eclipses and a prominent reflection effect. An analysis of the light-and radial velocity (RV) curves indicated a mass ratio of q = 0.1325, an RV semi-amplitude K = 47.2 km s -1, and an inclination of i = 72.33°. We show that a companion mass of 0.064 MŠ(tm), which is well below the hydrogen-burning limit, is the most plausible solution, which implies a mass close to the canonical mass (0.47 MŠ(tm)) of the sdB star. Therefore, the companion is a brown dwarf, which has not only survived the engulfment by the red-giant envelope but also triggered its ejection and enabled the sdB star to form. The rotation of J1622 is expected to be tidally locked to the orbit. However, J1622 rotates too slowly (vrot = 74.5 ± 7 kmâ‰ s-1) to be synchronized, challenging tidal interaction models. © 2014 ESO.
CRIS-Team Scopus Importer:2020-12-21
Keywords: Binaries: eclipsing; Binaries: spectroscopic; Brown dwarfs; Stars: fundamental parameters; Subdwarfs